A first look at the designs repair defence in Australia. (29th March 2019) - Berger, Tyrone
Abstract: GM Global Technology Operations LLC v SSS Auto Parts Pty Ltd [2019] FCA 97, Federal Court of Australia, 11 February 2019 The Federal Court of Australia has delivered the first judgment that reviews the repair defence in the Designs Act 2003, ruling that spare parts can be acquired for both repair and enhancement, and the defence should be available in such cases.